SEARCH AND RESEARCH MULTIBARYON CLUSTERING IN HADRON-NUCLEAR COLLISION AT HIGH ENERGY - Mamatova, Xolida; Sharofiddinov, Nodirbek (Физико-технологического образование, 2021)
The results obtained by analyzing the production of multibaryon clusters in π−C and p20Ne interactions at moments of 40 and 300 GeV/c, respectively, are presented.